2017
DOI: 10.3847/1538-4357/aa79a1
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Vertical Magnetic Field in Face-on Galaxies Using Faraday Tomography

Abstract: Faraday tomography allows astronomers to probe the distribution of the magnetic field along the line of sight (LOS), but that can be achieved only after the Faraday spectrum is interpreted. However, the interpretation is not straightforward, mainly because the Faraday spectrum is complicated due to a turbulent magnetic field; it ruins the one-to-one relation between the Faraday depth and the physical depth, and appears as many small-scale features in the Faraday spectrum. In this paper, by employing "simple to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 29 publications
(62 reference statements)
1
29
0
Order By: Relevance
“…As implied in the previous subsection, the global properties of galaxies (especially, this is the coherent, vertical magnetic field in this paper) can affect the shape of F(φ). As with the previous works [10,12], I use the width (standard deviation), skewness and kurtosis of F(φ) as shape-characterizing parameters to quantify the shape of F(φ). Here, I try to calculate the parameters only from the disk for the purpose to compare them with the simple galactic models.…”
Section: The Shape Of Faraday Spectrum Of External Galaxiesmentioning
confidence: 99%
See 3 more Smart Citations
“…As implied in the previous subsection, the global properties of galaxies (especially, this is the coherent, vertical magnetic field in this paper) can affect the shape of F(φ). As with the previous works [10,12], I use the width (standard deviation), skewness and kurtosis of F(φ) as shape-characterizing parameters to quantify the shape of F(φ). Here, I try to calculate the parameters only from the disk for the purpose to compare them with the simple galactic models.…”
Section: The Shape Of Faraday Spectrum Of External Galaxiesmentioning
confidence: 99%
“…As emphasized by Ideguchi et al [10], the study using the realistic Galactic model provides the realistic F(φ) of galaxies, but therefore, it is not straightforward to interpret the results due to its complexity. Following the studies by Ideguchi et al [10], Ideguchi et al [12] employ "simple, toy models" for the magnetic field in order for the deeper understanding of the behavior of F(φ). They found that the shape of F(φ) will converge to a well defined average by observing multiple LOSs covering a region of (10 coherent length of turbulence) 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The workshop had 64 participants. The biggest group of these were Japanese (24), there were 19 from Europe (6 Germany,4 Netherlands,4 Italy, 2 UK, 1 France, 1 Spain), 8 from North America (5 Canada, 3 US), 8 from Australia, and 4 from Asia other than Japan (2 South-Korea, 1 Russia, 1 India). A relatively large part of these were young researchers: 28 postdocs, 12 PhD students and 2 MSc students.…”
Section: Introductionmentioning
confidence: 99%